Green Marketing Practices of Selected Japanese Restaurants in Manila; Marketing Intervention - John Paul G. Buenaventura; Liberty B. Gutierrez (East Asian Journal of Multidisciplinary Research, 2023)
Environmentally conscious are further penetrating the restaurant industry. This study attempted to find out the answer whether green marketing practices have strong effects on the image of the company and customers’ behavioral intentions in the restaurant industry, another factor to consider were the demand and purchase of green products. Most of them projected it as an additional cost and same time customers would not demand or pressure them to be an environmentally friendly company. This would enable restaurants need to follow and implement existing practices and take the initiative to develop and sustain green marketing practices.